Comparison of middle phalanx of the middle finger and cervical vertebrae as skeletal maturity indicators - Pavitra Tripura Javangula; K S Uloopi; C Vinay; Chandrasekhar Rayala; N Manikya Kumar; S Pavani Chandra (Wolters Kluwer Medknow Publications, 2017)
Objectives: To investigate the relationship between chronological age and the stages of maturation of cervical vertebrae maturation index (CVMI) and the middle phalanx of the middle finger (MP3) and to determine the correlation between CVMI and MP3. Materials and Methods: A cross-sectional study included 100 children (boys - 50, girls - 50) aged 8-14 years based on nonprobability quota sampling. The study included digital radiographs of the MP3 of the right hand and conventional lateral cephalograms. Chronological age was assessed by the date of birth, MP3 maturation by Rajagopal and Kansal's criteria, and CVMI development by Hassel and Farman's method. Statistical Analysis: Spearman's rank-order correlation coefficient was applied to measure the association between stages of MP3 and CVMI. Results: Progressive stages of MP3 and CVMI were seen as chronological age advanced. Girls showed an advanced trend than boys in both MP3 and CVMI stages. MP3 and CVMI stages showed a strong positive correlation (r + 0.836, P < 0.01). Conclusions: MP3 and CVMI both are equally good indicators of skeletal maturity. Assessment of skeletal maturity on lateral cephalogram (CVMI) is advantageous as it avoids the need for an additional radiograph.